Fiscal Policy, Monetary Policy, and Trade Balance Nexus in Nigeria: A New Empirical Evidence - Nwagu, Godson Umunna; Orji, Anthony; Jude, Ikubor O.; Ogbuabor, Jonathan E.; Anthony-Orji, Onyinye I.; Nwufo, Lynda C. (Universitas Islam Indonesia, 2022)
Today fiscal and monetary policy instruments are inextricably linked in macroeconomic management as the macroeconomic variables are interwoven. The broad objective is to analyze the impact of fiscal and monetary policy instruments on the trade balance in Nigeria. This study uses the cointegration method and ordinary least square estimation to examine the impact of fiscal and monetary policy on Nigeria's trade balance from 1981 to 2018. The co-integration test confirms the existence of a long-run relationship between monetary policy as measured by broad money supply and fiscal policy as measured by government spending, taxation, and trade balance. The empirical findings revealed that the selected monetary and fiscal policy variables did not improve Nigeria's trade balance during the study period. As a result, the study recommended that the government encourage trade policies that increase exports to attract foreign exchange inflows and foreign investments.